(untitled) (gjstudies, 2020)
This research investigates the nuanced and often overlooked relationship between specific corporate governance configurations and the de facto independence of external auditors,moving beyond the traditional focus on formal regulatory compliance. While prior literature has extensively examined board independence and audit committee characteristics,this study introduces a novel, multi-dimensional framework that synthesizes elements fromagency theory, institutional theory, and behavioral economics to analyze governance as aninterconnected system. We posit that auditor independence is not merely a binary statebut a continuum influenced by a complex web of structural, relational, and cultural governance factors. Our methodology employs a unique, two-phase mixed-methods approach.First, we conduct a quantitative analysis of a proprietary dataset comprising governancemetrics, auditor tenure and fee data, and financial restatement histories for 450 publiclytraded firms over a ten-year period, utilizing a novel composite governance index we developed. Second, we perform a qualitative, in-depth case study analysis of twelve firmsidentified as outliers in the quantitative phase, employing semi-structured interviews withformer audit partners, board members, and CFOs to uncover the underlying mechanisms.Our findings reveal several counterintuitive insights. Contrary to conventional wisdom, wefind that excessively long audit committee tenure can, in certain governance climates, fosteroverly familiar relationships that subtly impair skepticism, a phenomenon we term ’tenureinduced complacency.’ Furthermore, we identify that the alignment (or misalignment) ofincentive structures between the audit committee and the full board—specifically regardingthe weighting of short-term earnings targets in compensation—creates a powerful, indirectpressure on auditors that is not captured by standard independence checks. The study alsodemonstrates that a high proportion of board members with financial expertise does notuniformly strengthen governance oversight; rather, its impact is contingent on the board’spsychological safety climate, which either enables or stifles critical challenge of management’saccounting judgments. These results contribute original theoretical and practical insights byreframing auditor independence as an emergent property of a dynamic governance ecosystem, with direct implications for the design of more resilient governance structures andregulatory frameworks aimed at enhancing financial reporting quality